(3eQBI GdeMGSfs - (3YHO GdbGOQ Hf eMeO Hf YHO GdbGOQ GdCejfs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO aEf eG jfHZi Cf jYJR Hg GdCYdGe hGdCcGHQ hJJMQc Hg CdSfI GdCbdGe ai CahGg GdeMGHQ eGgOi Zdi Mb hOd Ydi EQK eSJMb GdHGH GdChd ai PcQ GdTjN CHj GdeMGSf jhSa Hf eMeO QVi Gddg Yfg s
(3BNQgG (B:s
(3jfJgi HJQLeI GdTjN CHh YHO Gddg eMeO Hf ehSi GdeYQha HGdMLGL Hbhdg (B: (3hcGfJ haGJg SfI SHY hJSYjf hJSYeGFI QVi Gddg Yfge hfaYfG HHQcGJge CLeYjf s
(3HgG fXGe GdJYbjHIs
(3fSNI eLOhdI HGdCMeQ hYdjgG bQGAGJ hTQhMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI SjFI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs